A mechanistic approach to anti-nociceptive potential of Artemisia macrocephala Jacquem. Issue 1 (December 2016) - Shoaib, Mohammad; Shah, Ismail; Ali, Niaz; Shah, Wadood
Abstract Background Artemisia macrocephala Jacquem (A. macrocephala ), locally known as "Tarkha", is a perennial plant found abundantly in northern areas of Pakistan. It is widely used in traditional medicine to treat fever, pain, gastrointestinal disorders and diabetes. Till date, no published studies are available regarding the in-vivo antinociceptive potential of the crude extract and sub-fractions from the aerial parts ofA. macrocephala . Methods Antinociceptive effects of the crude methanolic extract and its sub-fractions were assessed using experimental pain models, including chemical nociception induced by intraperitoneal acetic acid or subplantar formalin injection and thermal nociception like tail immersion test in-vivo. Results The administration of various doses of crude extract and its fractions showed a dose-dependent indomethacin like antinociceptive effect in acetic acid induced writhing, subplantar formalin injection animal model suggesting the involvement of central mechanism of pain inhibition. Moreover, the crude extract and sub-fractions, on tail flick model (thermal nociception) demonstrated the involvement of central mechanism and significantly increased the latency time to 66.54, 82.94 and 70.53 %. The antagonistic study proposed the possible involvement of opioid receptor using naloxone as non-selective antagonist. The pharmacologically active chloroform and ethyl acetate fractions were further subjected to column chromatography that lead to the isolation four compounds. These isolated compounds were then subjected to various spectroscopic techniques upon which they were confirmed to be one sterol and three flavonoid derivatives. These findings suggest thatArtemisia macrocephala possesses peripheral and central analgesic potentials partially associated with opioid system that support its folkloric use for the management of pain. The isolated compounds are currently under investigation in our laboratory for analgesic activity and its possible mechanism of action. Conclusion The results in this study provide evidences thatA. macrocrphala has anticonciceptive effects and can be used for treatment of pain in traditional therapies. This study opens a new channel for isolation of analgesic compounds from the specie that is used traditionally for the management of pain.